Public-Oriented Graduate Quality Assurance as a Strategic Lever for Islamic Boarding School Competitiveness - Fauzi, Ahmad (Al-Qalam Institue, 2023)
This study aims to analyze graduate quality assurance as a strategic driver of competitiveness at Islamic Boarding School. Graduate quality assurance has become a central issue in global education, particularly in linking institutional reputation, character formation, and employability. However, research focusing on Islamic boarding schools remains limited despite their significant role in Indonesia’s education system. A qualitative case study approach was employed, using in-depth interviews, observations, and document analysis, with data analyzed through Miles and Huberman’s interactive model. Findings reveal three key outcomes. First, a structured graduate quality assurance system strengthens institutional reputation, enhancing trust among parents, government agencies, universities, and employers. Second, character-based quality assurance provides a unique competitive edge, as graduates are recognized not only for academic competence but also for integrity, discipline, and leadership. Third, employability emerges as an essential indicator, with graduates demonstrating adaptability, entrepreneurial skills, and readiness for diverse careers. These findings highlight that pesantren can integrate traditional values with modern quality frameworks, thereby achieving credibility and competitiveness in wider educational landscapes. The study contributes to expanding quality assurance discourse into faith-based institutions and recommends policy support to strengthen assurance systems in Islamic boarding schools.